2013
DOI: 10.4168/aair.2013.5.4.216
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus-Infected Epithelial Cells Produce More IL-8 and RANTES Compared With Other Respiratory Viruses

Abstract: PurposeThe environmental factors human rhinoviruses (HRVs) and house dust mites (HDMs) are the most common causes of acute exacerbations of asthma. The aim of this study was to compare the chemokine production induced by HRVs in airway epithelial cells with that induced by other respiratory viruses, and to investigate synergistic interactions between HRVs and HDMs on the induction of inflammatory chemokines in vitro.MethodsA549 human airway epithelial cells were infected with either rhinovirus serotype 7, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 33 publications
1
15
0
5
Order By: Relevance
“…These observations highlight a functional link of EV68 to the TLR3 signaling pathway. Intriguingly, EV68 infection stimulated IL-8 expression, similar to the case in rhinovirus infection (39). This phenomenon may be involved in the pathogenesis of virus-induced acute exacerbations of asthma (3).…”
Section: Discussionmentioning
confidence: 80%
“…These observations highlight a functional link of EV68 to the TLR3 signaling pathway. Intriguingly, EV68 infection stimulated IL-8 expression, similar to the case in rhinovirus infection (39). This phenomenon may be involved in the pathogenesis of virus-induced acute exacerbations of asthma (3).…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies have reported that the activation of the NF-κB pathway within A549 cells by various ssRNA viruses leads to the secretion of IL-8 and/or IL-6 (Arnold, Humbert, Werchau, Gallati, & Konig, 1994;Bao et al, 2007;Chun et al, 2013;Devhare, Chatterjee, Arankalle, & Lole, 2013;Julkunen et al, 2000;Kanzawa et al, 2006). Interestingly, all the ANK-R mutant MYXV constructs also stimulate NF-κB activation in A549 cells, but to varying degrees.…”
Section: Infection With Anks Knockout Myxoma Virus Triggers An Increamentioning
confidence: 95%
“…89 IL-8 is induced by various virus infections such as RSV, influenza A, and RV in airway epithelium. [90][91][92] CXCL-10/inducible protein-10 is produced by several cells such as monocytes, neutrophils, eosinophils, epithelial, endothelial, and fibroblast with response to IFN-γ. It can be induced by RV, RSV, influenza virus, etc., and have shown a protective role against pathogen infections.…”
Section: Bidirectional Interaction Of Asthma and Virus Infection-the mentioning
confidence: 99%